PENGEMBANGAN MODEL PEMBELAJARAN QUESTIONS STUDENTS HAVE PADA PEMBELAJARAN IPS DI SD/MI - Aulia Rika Harahap; Aninditya Sri Nugraheni (Universitas Islam Negeri Sumatera Utara, 2021)
Abstract: Development in the learning model always aims to get optimal learning outcomes. So, one of the models that the researcher developed was the Questions Students Have learning model which tested the extent of intellectual development and the characteristics of elementary school children. In learning, students get a lot of coverage, including providing direct experience to students, and being able to understand the material more deeply. This learning has implications not only for students but for teachers and the necessary infrastructure in schools. The results of the research at this stage showed good results where the development of the Questions Students Have learning model on social studies learning could stimulate interest, increase student learning motivation, require students to be actively involved and the students' response to learning. The response of students to learning models that can be expressed when learning activities are happy (90%) and those who say they are not happy are only (10%), as for the content of learning materials of students who say they are happy (80%), and who say they are not happy (20%), then the process of answering questions that stated happy or active (70%), while those who expressed displeasure (30%), and finally the learning atmosphere in class got a good response which was seen from the joy of the students (80 %) and those who expressed displeasure (20%). So it can be concluded that the Questions Students Have learning is feasible and good to use in the social studies learning model.